Incidence and Impact of Parvovirus B19 Infection in Seronegative Solid Organ Transplant Recipients. (17th January 2021) - Rezahosseini, Omid; Ekenberg, Christina; Møller, Dina Leth; Sørensen, Søren Schwartz; Wareham, Neval Ete; Perch, Michael; Gustafsson, Finn; Rasmussen, Allan; Kirkby, Nikolai; Reekie, Joanne; Lundgren, Jens; Nielsen, Susanne Dam
Abstract: Routine monitoring of parvovirus B19 (B19V) the first 6 months posttransplantation was performed in 241 seronegative solid organ transplant (SOT) recipients. Incidence rates during the first month and the second to sixth months posttransplantation were 1.2 (95% confidence interval [CI], .33–3.2) and 0.21 (95% CI, .06–.57) per 100 recipients per month, respectively. Of the 6 SOT recipients with positive B19V polymerase chain reaction, 3 (50%) were admitted to hospital and 2 (33%) were treated with intravenous immunoglobulin. Thus, routine monitoring of B19V in seronegative SOT recipients may not be necessary. Targeted screening 1 month posttransplantation and screening upon clinical suspicion could be an alternative strategy. Abstract : The incidence rate of B19V infection in seronegative solid organ transplant (SOT) recipients was low and routine monitoring of B19V in seronegative SOT recipients may not be necessary. Targeted screening 1 month posttransplantation combined with screening upon clinical suspicion could be an alternative strategy.